Generation of dengue 3 envelope domain III using tobacco mosaic virus-based vector system and its immunological response mouse model by generating anti-dengue virus antibodies: Tobacco mosaic virus-based dengue 3 domain III - Almohaimeed, Hailah M.; Assiri, Rasha; Aggad, Waheeb S. (Cellular and Molecular Biology, 2024)
Producing recombinant proteins in plants has become a valuable alternative to traditional microbial or mammalian systems due to its cost-effectiveness, scalability, and ability to perform post-translational modifications. This study investigates the use of the Tobacco Mosaic Virus (TMV)-based vector system for producing the Dengue virus serotype 3 (DENV-3) envelope domain III (EDIII) protein in plants.. A fragment of the gene that encodes domain III of the dengue 3 envelope protein (D3EIII, comprising 300-420 amino acids), was effectively expressed within Nicotiana tabacum plants utilizing a transient expression system based on tobacco mosaic virus (TMV). The N-terminal 5’ UTR region upstream of D3EIII notably enhanced protein yield in infected tissues. The produced recombinant protein exhibited reactivity with both (anti) D3EIII polyclonal antibodies and antibodies of anti-His tag. Upon injection of EDIII in mice, it stimulated the generation of antibodies against the dengue-specific virus. The induced antibodies demonstrated neutralizing activity against dengue virus type 3. These findings indicate that the TMV expression system is effective for producing dengue virus antigens in plants, resulting in antigens with appropriate properties and strong immunogenic potential.